Hybridization in ssDNA films - a multi-technique spectroscopy study - Howell, Caitlin; Zhao, Jianli; Koelsch, Patrick; Zharnikov, Michael (Physical chemistry, chemical physics, 2011)
A combination of X-ray photoelectron spectroscopy (XPS), high-resolution XPS, near-edge X-ray absorption fine structure (NEXAFS) spectroscopy, and sum-frequency-generation (SFG) spectroscopy was used to monitor two types of ssDNA films on Au(111) before and after hybridization. As probe systems, films of thiolated and block-oligonucleotides were used, taking thiolated thymine d(T) homo-oligonucleotides and thymine-adenine d(A-T) diblock-oligonucleotides as representative examples. In accordance with previous work, hybridization of the shorter and more densely packed thiolated ssDNA films produced fewer (if any) hybrids, whereas the longer and less densely packed layers exhibited a larger hybridization yield. The above effects were less pronounced in the case of the d(A-T) films where the hybridization yield of the less densely packed monolayers was significantly lower. This was presumably due to the formation of internal dimeric hybrids in the immobilization step of the probe molecules, resulting in the generation of fewer probe-target hybrids upon exposure to the target molecules. In all ssDNA films displaying a reasonable number of hybrids present, significant orientational changes were observed and could be monitored in detail. These results suggest that the given combination of spectroscopic techniques can be a valuable tool to gain molecular-level information about hybrids at interfaces.
Gesehen am 30.06.2022